The Influence Digital Marketing and Market Orientation on Marketing Performance Moderated by Competitive Advantage - Agustina, Lia; Hadi, Prasetyo; Jubaedah, Jubaedah; Setiadi, Iwan Kresna (Quantitative Economics and Management Studies, 2024)
The phenomenon in this research is the decline in the number of marriage registrations at Ministry of Religious Affairs/KUA. According to data from the Indonesian Ministry of Religion in the last three years, the marriage rate in Indonesia has decreased drastically. Around two million marriages will decrease by 2024. Meanwhile, according to the 2018 in the Central Statistics Agency (BPS) report, the creative economy subsector contributes greatly to the national economy, with a contribution of 7.44% to Gross Domestic Product (GDP), one of the MSMEs in the creative economy subsector namely MSME EO. With the decline in the number of KUA registrations, MSMEs in the marriage sector are experiencing market saturation. Therefore, marketing performance (variable y) is required, including competitive advantage (variable z) as moderation and (variable x) namely digital marketing and market orientation. This research used quantitative and saturated sampling techniques. The population involved 101 MSME actors in the field of Event Organizer (EO) in DKI Jakarta. Employing SMART PLS 4.0, the results of this research indicate that digital marketing and market orientation have a significant influence on EO marketing performance in DKI Jakarta. However, competitive advantage cannot moderate digital marketing and market orientation.